Matlab/Simulink Modeling of Four-leg Voltage Source Inverter With Fundamental Inverter output Voltages Vector Observation - Omar, Riyadh G.; Thejel, Rabee' H. (Iraqi Journal for Electrical and Electronic Engineering, 2014)
Four-leg voltage source inverter is an evolution of the three-leg inverter, and was ought about by the need to handle the non-linear and unbalanced loads. In this work Matlab/ Simulink model is presented using space vector modulation technique. Simulation results for worst conditions of unbalanced linear and non-linear loads are obtained. Observation for the continuity of the fundamental inverter output voltages vector in stationary coordinate is detected for better performance. Matlab programs are executed in block functions to perform switching vector selection and space vector switching.